УЛС ТӨРИЙН ОНОЛ, ФИЛОСОФИ, ҮЗЭЛ СУРТАЛ ГЭЖ ЮУ ВЭ? - Ё.Довчин, (Politology, 2023)
In the article, the author intended to reveal interdependence and specifics of the categories of political theory, political philosophy and political ideology. Political theory development and various concepts of fundamental researchers in the West are being compared in the article. Linguistics role in political theory, development and relationship between words and concepts are being defined.